Research on Xiaoyao Powder in the treatment of depression based on epigenetics and quality markers - Wang, Jiayun; Wu, Qiaolan; Ou, Chunxue; Lu, Guangying; Yu, Huayun (Frontiers in Neuroscience, 2023)
Abstract：Depression has become one of the most common public health issues around the world, the incidence has been increasing lately. A large amount of clinical investigates have proven that the treatment of depression is difficult. The prognosis is poor, and the fatality rate is high. At present, the Western medicine is the preferred treatment for depression, but it often causes clinical adverse reactions such as dry mouth, blurred vision and memory loss, et al. The herbal compound Xiaoyao Powder is a traditional medicine for soothing the liver and relieving depression, strengthening the spleen and nourishing the blood, and it can reduce adverse reaction. It is effective in treating depression. In this study, we elucidate the function of Xiaoyao Powder in anti-depression from the perspective of clinical application, the pharmacological mechanisms such as regulating epigenetic and chemical quality markers in order to provide empirical and experimental theoretical which can hold out the therapy in depression with Xiaoyao Powder in the future.